Preparation of a model for the establishment of private higher education institutions using statistical indicators - Obed Mahmood Muhsin; Hatem Hatef Abdulkadhim; Mukhtar Ali Farhan (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
The importance of education is realized everywhere and is now on top of the political agenda of most nations. Higher education plays a governance role in education. Many interested bodies have set out their views about how quality assurance and regulation should evolve in order to meet the required standard. Statistical indicators play a vital role in assessing the activities of higher education institutions and improving and consolidating the educational system. This research is intended to suggest a set of qualitative statistical indicators for assessing the quality of higher education institutions. In this paper, ten indicators were proposed for higher education institutions. One of the advantages of the proposed indicators is their ability to be modified by the user. Conclusions and numerical results were then reported.